Use of microﬂuidic organ-on-a-chip systems for the screening and development of phytopharmaceuticals and herbal drugs - Shahabipour, Fahimeh; Aldhaher, Abdullah; Doseff, Andrea I.; Alavian, Seyed Ehsan; Elnour, Adam Hassan Mohammed; Ashammakhi, Nureddin (Elsevier, 2023)
Natural products (NPs) and their derivatives constitute an important source of bioactive pharmaceutical compounds. Due to the increasing interest in NPs, finding new approaches for rapid screening of novel chemistries and evaluating their potential toxicity is of paramount significance. The extensive repertoire of NPs and derivatives and their presence as complex mixtures presents challenges at multiple levels, including the screening for the bioactive components and real-time detection of drugs effects. Recent advances in microfluidic approaches such as organ-on-a-chip, Herbochip, microfluidic biochip, and multiorgan-on-chip have been developed to facilitate the real-time detection of drug effects on cancer cells. Microfluidic devices enable high throughput and reliable detection of drug cytotoxicity in cell-free systems. Here, we review different microfluidic devices, such as Herbochip and organ-on-chip. The impact of these devices is to identify active components from herbal extraction, the potential of helping to understand the mechanisms of botanical drugs, and determining cytotoxicity of new lead compounds. We also highlight the influence of microfluidic devices, such as organ-on-chip and Herbochip, in translating NP activities into the development of drugs toward precision medicine.